Characterisation of probability learning in a rural environment with the realistic mathematics education (2022)
Background: As statistics has pragmatic effects in other sectors, this work argues for proposing teaching-learning strategies based on real situations. Objectives: Characterise probability learning in a rural environment with realistic mathematics education. Design: Of a qualitative nature with an action-participatory research design, through five methodological phases. Setting and participants: Students from rural areas of the department of Córdoba-Colombia, the mathematics education teacher of that department, and the research group. Data collection and analysis: The qualitative data were grouped into categories of realistic mathematics education. Results: The research revealed that the students present interpretive, theoretical, and algorithmic difficulties. It also highlighted that realistic mathematics education reflects human activity in the statistical learning process. Conclusions: The contextualised problems allow students to reach meaningful knowledge. Besides, the teacher cooperates in formalising learning due to its structuring, systematisation, and regularisation under the realistic mathematics education criteria.